Development of an e-comic on biotechnology materials in high school - Juliarti; Ruqiah Ganda Putri Panjaitan; Titin (Biosfer: Jurnal Pendidikan Biologi, 2026)
Biology learning in biotechnology materials already incorporates practical activities, but the limitations of the media and visual representations remain obstacles to students' understanding. Therefore, media development e-comic potentially facilitate learning through a combination of interesting images, text, and stories. This research aims to determine students' eligibility and responses to the media e-comic, which includes biotechnology materials, as well as to explore its potential as an attractive educational resource. This research uses a modified research & development methodology based on Borg & Gall, adapted by Sugiyono. Selecting participants through purposive sampling, involving 20 tenth-grade high school students. This research uses validation sheets and student response questionnaires. The research instrument was validated by 5 expert validators. Using Aiken's V formula to analyze the data collected during the study. Reliability testing using intraclass correlation coefficients. Assessment of student response questionnaires using the Likert scale. Media validation analysis obtained an average value of 0.92, which is included in the valid category. Reliability test showing a reliability value of 0.946, which belongs to the excellent category. The assessment of student responses had an average score of 78.63%, indicating a good category. These results show that the media e-comic biotechnology materials received a positive response from students, and the media e-comic was effectively used in the learning process.